Platelet Ca2+ Homeostasis: Na+-Ca2+ Exchange in Plasma Membrane Vesicles - Rengasamy, Appavoo; Soura, Soudabeh; Feinberg, Harold (Thrombosis and Haemostasis, 1987)
A vesicular plasma membrane-enriched fraction obtained from human platelets exhibited 45Ca2+ uptake in exchange for intravesicular Na+. The rate of Ca2+ uptake was linear up to 4 sec. The apparent Km for Ca2+ was 22 pM and the Vmax 280 pmol/mg/ sec. Ca2+ efflux from Ca2+ loaded vesicles was obtained upon dilution into a NaCl but not a KC1 medium. The extent of Ca2+uptake was monotonically increased as the pH increased from 6 to 9. Na+-Ca2+ exchange was shown to be electrogenic. Ca2+ uptake was distinguished from binding by the induction of Ca2+ release after A23187 addition. These findings support a role for Na+-Ca2+ exchange in human platelet Ca2+ transport.
Keywords: Platelets; Ca2+ homeostasis; Plasma membrane; Na+-Ca2+ exchange